To the ends of the earth - Bunn, T. Davis, 1952- (T. Nelson, 1996)
In a story set in the Roman Empire following the death of the emperor Constantine, power struggles erupt in the outer reaches of the empire and Travis and his father Cletus, who manage a Roman consul's estate in Africa, fight to stay alive